Factor structure of the Body Image Concern Inventory in a Japanese sample. (March 2015) - Tanaka, Masanori; Tayama, Jun; Arimura, Tatsuyuki
Highlights: This study tested the second-order factor model of the BICI in a Japanese sample. The result showed that this model was an adequate fit to the data. This model was consistent across genders controlling for measurement invariance. Abstract: The purpose of this study was to investigate the factor structure of the Body Image Concern Inventory (BICI) using a Japanese population as a web-based survey. Two thousand and sixty individuals (1030 women, 1030 men) ranging from 20 to 69 years of age ( M = 40, SD = 16) took part in the present research. A confirmatory factor analysis showed that the second-order factor model of the BICI, which had three first-order factors and one second-order factor of dysmorphic appearance concern was an adequate fit to the data. Additionally, the Cronbach's alpha values of the overall and three subscales of the BICI were adequate. Furthermore, measurement invariance tests revealed that the second-order factor model of the BICI had acceptable measurement invariance at the scale and factor-loading levels between genders. These findings suggested that the BICI was reliable, and able to compare its mean scores between women and men in Japan.